African Languages and Linguistics - (:unkn) unknown (My University, 2015)
Linguistique et Langues Africaines (LLA) [African Languages and Linguistics] is an international journal for African linguistics, whose main goal is to contribute to a better knowledge of languages spoken in Sub-Saharan Africa, be they vernacular, vehicular or creole, with the exception of local varieties of European languages. We are open to recent trends and all theoretical approaches. The selected articles may be chiefly concerned with linguistic domains (e.g. phonology, morphology, syntax, lexicography and semantics), or include an anthropological component. Contributions providing comparative or typological approaches are also welcome. Junior researchers (e.g. PhD students) are encouraged to submit their contributions to LLA. Linguistique et Langues Africaines is particularly interested in publishing analyses based on fieldwork data as well as studies relating to little documented or endangered languages and cultures. The journal is also open to contributions that are less concerned with theory, such as working documents or firsthand data; such research will appear in a special “notes and documentation” section. Our journal also includes book reviews. The languages of the journal are English and French, as well as other major European languages (please consult the editors). Submissions to “Linguistique et Langues Africaines” undergo a double-blind peer review by experts who are not members of the editorial board. The second issue of our journal is scheduled for the end of 2016.
Keywords: African Research